Synthesis, Selective Cancer Cytotoxicity and Mechanistic Studies of Novel Analogs of Lantadenes - Tailor, Navin K.; Jaiswal, Varun; Lan, San Swee; Lee, Hong Boon; Sharma, Manu (Anti-Cancer Agents in Medicinal Chemistry, 2013)
The ring A and D substituted analogs of pentacyclic triterpenoid Lantadene A (1) and B (2) were synthesized and evaluated for in vitro anticancer activity against four human cancer cell lines (HL-60, MCF-7, A549 and HCT-116). Analogs 3, 4, 7 and 8 showed enhanced inhibitory activity as compared with 1 and 2. These analogs were found more active than standard drug cisplatin with selective toxicity towards cancer cells and were inactive against normal cells (VERO). Furthermore, the mechanistic studies to investigate the effects of the new compounds on Akt protein in lung cancer cell line A549 and the NF-κB signalling pathway suggested that the compounds may exert their inhibitory activity on cancer cells through inhibition of both Akt and NF-κB activation. The docking studies of most potent analog (7) with 3D crystal structure of the nuclear factor kappa-B (NF-κB) P50 homodimer (PDB ID: 1NFK) revealed that carbonyl group of ester side chain and C-28 carboxylic acid groups were mainly involved in hydrogen bonding interaction. The oleanane frameworks was involved in strong hydrophobic interaction with amino acid phenylalanine and structure of lead compound have the potential to be developed as potent NF-κB inhibitor and anticancer agent.
Keywords: NF-κB